DATABASE COMPONENTS OF THE POLYTECHNIC UNIVERSITY TYPICAL INFORMATION RESOURCES INTERNET PORTAL - Babenko, B.O.; Babina, T.B.; Gabzovska, О.Б.; Savitsky, А.Й. (Journal of Information Technologies in Education (ITE), 2010)
Typical information resources database components for polytechnic university portal are showed. Information resources database structure is presented as aggregate of thesaurus, collections, and reference books.